Comprehensive analysis of evolution of serrated hysteresis loops of Alloy 617 M during low cycle fatigue. (December 2022) - Shankar, Vani; Kumar, Anish
Abstract: Dynamic strain aging (DSA) has a pronounced effect on low cycle fatigue (LCF) behavior of materials. One of the manifestations of occurrence of DSA under LCF is serrated hysteresis loops (HLs). Analysis of the evolving serrated HLs under LCF loading has a large potential to provide information on the underlying principles of the occurrence of DSA. However, as manual analysis of serrated HLs is cumbersome, it has not been studied so well. A methodology for automated analysis of the serrated flow behavior under LCF loading is developed and used in the present paper for comprehensive analysis of evolution of DSA behavior in Alloy 617M during low cycle fatigue. For the first time, the magnitude of the evolving serrations both within a cycle and through the entire fatigue life has been represented as 2D stress drop maps to visualize the scale of DSA occurrence at any moment within the entire fatigue event for a given strain amplitude-temperature combination. Quantitative characterization of serrated behavior is reported as a function of fatigue cycle for different total strain amplitude and temperature combinations. Critical parameters for the initiation of DSA determined by stress drop and strain jump methods indicate a progressive nature, typical of fatigue deformation. Pronounced DSA activity at 773 K as compared to that at 573 K and 973 K is also reflected in terms of micro-strain in deformed specimens as observed by electron back-scatter diffraction (EBSD) analysis. Graphical Abstract: ga1 Highlights: Methodology is proposed for comprehensive study of evolution of DSA during LCF. Visualization of scale of DSA at any moment within entire fatigue event as 2D maps. Dynamic nature of DSA with strain cycling under LCF is observed. Optimum plastic strain-temperature-cycle number combination only initiates DSA. Most conducive temperature for DSA occurrence in Alloy 617 M during LCF is 773 K.